Utilization of differentiated instruction in K-12 classrooms: a systematic literature review (2000–2022) - Hu, Linlin (Asia Pacific education review, 2024)
Differentiated instruction (DI) is a beneficial approach to addressing students’ diverse learning needs, abilities, and interests to ensure that each student has the opportunity to make academic progress. To answer the question of how teachers utilize DI in K-12 classrooms, this systematic review was based on 61 empirical studies on DI published between 2000 and 2022. It examined the current status and trends of implementing DI in K-12 education and integrated various factors involved in the process of DI, including educational levels, subjects, student difference analysis, instructional methods, content, tools, assessment methods, and instructional effectiveness. The findings indicated that (1) DI was most commonly used in primary school mathematics and language classrooms, with the majority of studies having sample sizes exceeding 100 and lasting for more than 6 months; (2) The most frequently employed form of DI was ability grouping, often grouped based on academic achievement; (3) Information technology tools and resources can empower differentiated instruction; (4) Most studies utilized standardized tests, questionnaires, and scales as evaluation tools, with a focus on the impact of DI on students’ academic achievement and skills; and (5) The effectiveness of DI was controversial and influenced by multiple factors, such as may be associated with the instructional methods. In response to these findings, the study introduces a comprehensive DI model. This model, rooted in the perspective of instructional design, elucidates the interconnected factors of DI. It serves as a valuable reference for the future design and implementation of DI, offering a practical guide for educators aiming to create inclusive and effective learning environments.